Studying the interrelationship between clouds and solar radiation - Waled Alrjbo; Mustafa Mohammed (College of Education for Pure Sciences, 1999)
Abstract There are a few studies concerning the interference between solar radiation and the different types of clouds in Iraq generally and in Mosul especially, and this gives an importance to perform this research. The most important results obtained from this research are: • We observed the dominance of the following types of clouds in Mosul sky during the period (Aug-2007-July2008): Cumulus cloud (Cu( during Summer months, Altocumulus cloud (Ac) and Cumulus cloud (Cu) during Autum months, strato cumulus cloud (Sc) during winter months, Cirrus (Ci) and Cirros stratus (Cs) and Cumulus clouds during the spring months. • The mean values of transmissivity for the following clouds (Ci,Cs,Cs+Cu,As,Sc,Sc+Cu,Sc+As) were (75,77,72,57,35,42,51)% respectively. • Correlations between the solar radiation intensity transmitted through the different types of clouds and its intensity under clear sky were found, the correlation coefficient of these relations are ranged between(0.96-0.99).